(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the translation of saj’s in the texts of «Boburnoma», originally used in the original text of the English translations of Leiden-Erskine, A.S.Beveridge and W.Thackston. It is also mentioned that saj’ expressions in the text should be replaced with alternatives related to the target language. It also discusses the selection of rhymed and weighted forms of saj’, their reflection in the text, the importance of preserving the spirit of originality in translation.